2018
DOI: 10.1080/08952841.2018.1444937
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life as a mediator of leisure activity and perceived health among older women

Abstract: Despite consistent evidence to suggest that participating in leisure is associated with perceived health status among older adults, there have been few attempts to determine the possible underlying mechanisms in this relationship, including the role of quality of life (QoL). This study examined the role of perceived quality of life in the relationship between leisure and perceived health in older women. Correlations, regression, and mediation analysis were conducted on data from the Woman's College Alumnae Wom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 70 publications
0
13
0
1
Order By: Relevance
“…Kim and Kim found that fencing participants gained emotional satisfaction from fencing through learning how to overcome difficulties and solve problems, which also boosted their confidence [42]. Eifert, Hall, Smith, and Wideman determined that emotional satisfaction increases when physical function develops and achievements are reached, and the emotional satisfaction has the positive impact of increasing focus on exercise [43]. Ahn, as well, identified that participating in leisure activities relieves stress and contributes to self-improvement and self-development, which ultimately benefits societies [44].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kim and Kim found that fencing participants gained emotional satisfaction from fencing through learning how to overcome difficulties and solve problems, which also boosted their confidence [42]. Eifert, Hall, Smith, and Wideman determined that emotional satisfaction increases when physical function develops and achievements are reached, and the emotional satisfaction has the positive impact of increasing focus on exercise [43]. Ahn, as well, identified that participating in leisure activities relieves stress and contributes to self-improvement and self-development, which ultimately benefits societies [44].…”
Section: Discussionmentioning
confidence: 99%
“…Petrick and Backman found that leisure satisfaction and the need for interpersonal relationships were affected by social friendliness and interactions, and Shin and Kim found that unmarried women spent much time during their weekends on interpersonal social activities such as meeting friends and colleagues [54,55]. Eifert, Hall, and Wideman also found that women's participation in physical activity had high positive effects on their interpersonal satisfaction [43].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, our results indicated a potential bene cial effect of CLAIs on reduced mortality risk among participants who were diagnosed with cardiovascular or metabolic disease (HR = 0.67, P = 0.025 in univariate analysis, HR = 0.69, P = 0.054 in multivariate analysis, Figure 3). Accumulating evidence has indicated that leisure activity, including watching TV 20 , internet use 21 and reading 22,23 , can make a signi cant contribution to overall life satisfaction and psychological well-being 24,25 , which is subsequently associated with a lower risk of cardiovascular disease 61,62 . Thus, a potential pathway by which cognitive leisure activity in uences all-cause mortality may be through reducing the risk of cardiovascular disease or reducing the effect of cardiovascular disease on mortality.…”
Section: Discussionmentioning
confidence: 99%
“…It is projected that, by 2050, 1.6 million or 43% of older adult deaths will be due to dementia and Alzheimer's disease 19 . In addition, accumulating evidence has indicated that leisure activity, including watching TV 20 , internet use 21 and reading 22,23 , can make a signi cant contribution to overall life satisfaction [24][25][26] , which has been identi ed as an important risk factor for mortality in older people [27][28][29] . Recently, a prospective cohort study indicated that playing cards or mahjong and reading were association with lower all-cause mortality in the Chinese oldest-old population 30 .…”
Section: Introductionmentioning
confidence: 99%
“…3). Accumulating evidence have indicated that leisure activity, including watching TV 20 , internet use 21 and reading 22,23 , can make a signi cant contribution to overall life satisfaction and psychological well-being 24,25 , which in turn is associated with lower risk of cardiovascular disease 58,59 . Thus, a potential pathway by which mental activity in uence all-cause mortality may be through reducing the risk of cardiovascular disease or reducing the effect of cardiovascular disease on mortality.…”
Section: Discussionmentioning
confidence: 99%